Is Assisted Reproductive Technique Shari'aa-compliant? A Case Study at a Fertility Centre in Malaysia - Ahmad Murad, Zainuddin; Zailin Shah, Yusoff; Mansor, Sulaiman; Ahmad Irfan, Ikmal Hisham; Abdullah, Long (IMJM, International Islamic University Malaysia, 2014)
Introduction: To investigate the questions that Muslim patients, embryologists, paramedics, clinical counsellor and doctors may have pertaining to the compliance of Assisted Reproductive Technique (ART) to Shari’aa. Methods: As a preliminary study, an open-ended survey was administered to participants. Participants for the survey comprised of 21 patients, 2 embryologists, 2 doctors, 4 paramedics and 1 counsellor. Results: Data analysis showed that most of the participants posed questions that fall into six classifications which are: Munakahat (Family Law), social Hukm, Fiqh Ibadah, Fiqh Qadha (Islamic Hukm), General Fiqh and Usul Fiqh. Conclusion: It is clear that even though the participants were rather familiar with some of the existing Fatwas pertaining to ART and IVF in Malaysia, there are still remaining doubts which need to be clarified. This indicates that there are challenges faced in seeking and providing ART treatment to Muslim patients. This needs to be addressed perhaps in the form of Shari’aa-compliant guidelines to provide a clear explanation of each process and procedure in fertility treatment.